Revitalization Program Of The Market In Improving Infrastructure Development And Participation Of The Market Traders - Sufi Hamdani Kurniawan; Sri Kusriyah Kusriyah (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Revitalization program aims to establish a public market in terms of both infrastructure or welfare of the traders in the market people. The method used in this study explorative inductive data collection techniques of observation, interviews and documentation. The data obtained by the guidelines as an informant interviews are officials and employees in the Department of Industry and Trade as well as traders in local markets. To help revitalize local markets to improve infrastructure and to be implemented properly in requiring the active participation of traders. With a good governance of each program can be run and supported by community participation.Keywords: Market Revitalization Program; Infrastructure Development; The Participation Of Traders.